Kaidah Mutarâdif al-Alfâz dalam al-Qur’an - Fawaid, Ahmad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
a phenomenon that occurs in Arabic, even did not rule contained in almost all languages on earth. As an Arabic text, whether the Koran cannot duck and dodge the fact tarâduf growing presence in the Arabic tradition? In other words, if the Koran also collects some words lexical meanings which have in common sense? Or whether every word that has the same meaning in the Koran cannot be equated entirely? Therefore, the wording in the Koran, in addition to having specificity in every meaning also has a different meaning to the other and the word has suitability in order. This article appeared before the readers to explain the words which have been considered to have the same meaning in the Koran from the perspective of linguistic science and the Koran.